Global, regional and national burden of infections among pregnant women, 1990–2021: a prospective cohort study - Wei Xu; Xiao Hu; Chen Li; Liming Cheng; Meiyi Chen; Siqiao Wang; Shun Chen; Zhourui Wu; Zhihui Xiao; Bei Ma (BMJ Open)
Objectives We aimed to analyse the trends, age distribution and disease burden of maternal sepsis and other maternal infections (MSMI) to improve management strategies.Design We extracted data from the global burden of disease (GBD) 2021 database to evaluate MSMI burden with different measures for the whole world, 21 GBD regions and 204 countries from 1990 to 2021.Setting Studies from the GBD 2021 database generated by population-representative data sources identified through a literature review and research collaborations were included.Participants Patients with an MSMI diagnosis.Outcomes Total numbers, age-standardised rates (ASRs) of incidence, prevalence, mortality and disability-adjusted life years (DALYs) on MSMI from the GBD 2021 study and their estimated annual percentage changes (EAPCs) were the primary outcomes.Results There were 19 047 404 (95% uncertainty interval (UI) 14 608 563 to 24 086 486) annual incident cases, 2 376 876 (95% UI 1 678 868 to 3 421 377) prevalent cases at a single time point, 17 665 (95% UI 14 628 to 21 191) death cases and 1 144 233 (95% UI 956 988 to 1 352 034) DALYs of total MSMI in 2021. From 1990, the case number and ASRs of incidences and prevalence showed decreasing trends, while the case number and ASRs of mortality and DALYs gradually increased with time, reaching the peak in 2001, and then declined. In 2021, the ASRs of incidence, prevalence, mortality and DALYs sharply increased with age, which reached the peak in the 20–24 age group. The ASRs were decreased with increasing sociodemographic index (SDI). In 2021, it showed a positive correlation between EAPC and ASR of DALYs (r=0.3398, p<0.001).Conclusions The disease burden in low-SDI regions far exceeded that of regions with higher SDI. The persistent disparities in the burden of MSMI between low- and high-SDI regions underscore the urgent need for context-specific interventions, including targeted healthcare infrastructure investments in central and western sub-Saharan Africa, integration of WHO’s Maternal Sepsis Guidelines into national policies, and prioritisation of antenatal care access for women aged 20–24 years. These strategies align with sustainable development goals to reduce maternal mortality and achieve universal health coverage by 2030.